Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's solve the problem step-by-step.
### Part (a) - Finding the zeros of the function
To find the zeros (roots) of the function [tex]\( f(x) = x^2 - 7x \)[/tex], we need to solve for [tex]\( x \)[/tex] when [tex]\( f(x) = 0 \)[/tex].
Set [tex]\( f(x) \)[/tex] equal to zero:
[tex]\[ x^2 - 7x = 0 \][/tex]
Factor the quadratic equation:
[tex]\[ x(x - 7) = 0 \][/tex]
Set each factor equal to zero:
1. [tex]\( x = 0 \)[/tex]
2. [tex]\( x - 7 = 0 \)[/tex]
Solving these for [tex]\( x \)[/tex] gives us:
[tex]\[ x = 0 \][/tex]
[tex]\[ x = 7 \][/tex]
So, the zeros of the function are:
[tex]\[ x = 0, 7 \][/tex]
### Part (b) - Verifying the results algebraically
To verify the results, we will use the same equation and factor it.
Start with the original function:
[tex]\[ f(x) = x^2 - 7x \][/tex]
We already factored it in part (a):
[tex]\[ x(x - 7) = 0 \][/tex]
Setting each factor to zero, we get:
1. [tex]\( x = 0 \)[/tex]
2. [tex]\( x = 7 \)[/tex]
Thus, the zeros of the function are confirmed once again to be:
[tex]\[ x = 0, 7 \][/tex]
Hence, the zeros of the function [tex]\( f(x) = x^2 - 7x \)[/tex] are indeed [tex]\( x = 0 \)[/tex] and [tex]\( x = 7 \)[/tex].
The factorization also agrees with this:
[tex]\[ x^2 - 7x = x(x - 7) \][/tex]
Now let's summarize the answers:
(a) The zeros of the function are:
[tex]\[ x = 0, 7 \][/tex]
(b) Verified results algebraically:
[tex]\[ x = 0, 7 \][/tex]
### Part (a) - Finding the zeros of the function
To find the zeros (roots) of the function [tex]\( f(x) = x^2 - 7x \)[/tex], we need to solve for [tex]\( x \)[/tex] when [tex]\( f(x) = 0 \)[/tex].
Set [tex]\( f(x) \)[/tex] equal to zero:
[tex]\[ x^2 - 7x = 0 \][/tex]
Factor the quadratic equation:
[tex]\[ x(x - 7) = 0 \][/tex]
Set each factor equal to zero:
1. [tex]\( x = 0 \)[/tex]
2. [tex]\( x - 7 = 0 \)[/tex]
Solving these for [tex]\( x \)[/tex] gives us:
[tex]\[ x = 0 \][/tex]
[tex]\[ x = 7 \][/tex]
So, the zeros of the function are:
[tex]\[ x = 0, 7 \][/tex]
### Part (b) - Verifying the results algebraically
To verify the results, we will use the same equation and factor it.
Start with the original function:
[tex]\[ f(x) = x^2 - 7x \][/tex]
We already factored it in part (a):
[tex]\[ x(x - 7) = 0 \][/tex]
Setting each factor to zero, we get:
1. [tex]\( x = 0 \)[/tex]
2. [tex]\( x = 7 \)[/tex]
Thus, the zeros of the function are confirmed once again to be:
[tex]\[ x = 0, 7 \][/tex]
Hence, the zeros of the function [tex]\( f(x) = x^2 - 7x \)[/tex] are indeed [tex]\( x = 0 \)[/tex] and [tex]\( x = 7 \)[/tex].
The factorization also agrees with this:
[tex]\[ x^2 - 7x = x(x - 7) \][/tex]
Now let's summarize the answers:
(a) The zeros of the function are:
[tex]\[ x = 0, 7 \][/tex]
(b) Verified results algebraically:
[tex]\[ x = 0, 7 \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.